PERAN KELUARGA KATOLIK DALAM MENGHADIRKAN GEREJA MENURUT KARDINAL DARMOJUWONO - Agustinus agus widodo (Jurnal Teologi (Journal of Theology), 2012)
This main aim of this research is to comprehend the ecclesiastical vision of Cardinal Darmojuwono, the Archbishop of Semarang (1964-1981). On the one side, inspired by the Second Council, he desired and tried to establish the Archbishop of Semarang as autonomous people of God, not only restricted to the internal autonomy, but also to others, outside the Archdiocese of Semarang. In internal scope of the Catholic Church, such effort was done by fostering the spirit of missionary. On the other side, he developed the Church in social external scope, such movement was realized by the involvement of te Church in the society. So, it is inferred that Cardinal Darmojuwono had an ecclesiastical vision to establish a Church which is autonomous, missionary, and society-involved. In order to realized that ecclesiastical vision agents, he underlined the role of Christian families. They are not only the smallest sociological group but also the implementation and the experience of Gods Kingdom in the society.